ANALISIS METODE CHEATING PADA TES BERSKALA BESAR - Yance Manoppo; Djemari Mardapi (Program Studi Pendidikan Kimia FKIP Universitas Pattimura, 2019)
This study aimed to reveal: (1) the characteristics of items of Chemistry Test in National Examination by using the classical test theory and item response theory; (2) the amount of cheating which occured by using Angoff's B-index Method, Pair 1 Method, Pair 2 Method, Modified Error Similarity Analysis (MESA) Method, and G2 Method; (3) the methods that detect more cheating in the implementation of the Chemistry Test in National Examination for high schools in the year 2011/2012 in Maluku Province. The results of the analysis with the classical test theory approach show that 77.5% items have item difficulty functioning well, 55% items have discrimination yet qualified and 70% items have distractor that works well with the index reliability test of 0,772. The analysis using the item response theory approach shows that 14 (35%) items fit with the model, the maximum function information is 11,4069 at Î¸ = -1,6, and the magnitude of the error of measurement is 2,296. The number of pairs who are suspected of cheating is as follows: 13 pairs according to Angoff's B-index Method, 212 pairs according to Pair 1 Method, 444 pairs according to Pair 2 Method, 7 pairs according to MESA Method, and 102 pairs according to G2 Method. The most widely detecting cheating in a row is a Pair 2, Pair 1, G2, Angoff's B-index, and MESA.